Answer:
4x+2 34/7 -6/7
--------- = ------------ +--------
( x-8) (x-1) ( x-8) (x-1)
Explanation:
4x+2
---------
x^2−9x+8
Factor the denominator
x^2 -9x +8 = ( x-8) (x-1)
4x+2 A B
--------- = ------------ +--------
( x-8) (x-1) ( x-8) (x-1)
Multiply each side by ( x-8) (x-1)
4x+2 = A ( x-1) + B ( x-8)
4x+2 = Ax -A + Bx - B8
Making two equations
4x = AX + Bx
Factoring out the x
4 = A + B
2 = -A - 8B
Adding these equation to eliminate A
4 = A + B
2 = -A - 8B
--------------------
6 = -7B
-6/7 = B
Now finding A
4 = A -6/7
4 + 6/7 = A
28/7 + 6/7 = A
34/7 = A
4x+2 34/7 -6/7
--------- = ------------ +--------
( x-8) (x-1) ( x-8) (x-1)